Analisis Konsumsi Mahasiswa UIN Sumatera Utara dalam Gaya Hidup Sehari-hari - Lusi Ramadianti; Miftah Rizki (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
A pleasure-seeking lifestyle is a lifestyle that places pleasure above all else. Many individuals, including students, live such a lifestyle. The purpose of this study is to understand the factors that encourage students of UINSU's Sharia Accounting Department in Medan City to tend to choose a lifestyle that prefers pleasure, and to find out the views of Islamic Economics regarding this behavior. This research was conducted qualitatively using a phenomenological approach. The findings indicate that the decisive factors that influence self-care habits among students who specialize in Sharia Accounting can be divided into two categories: internal and external. Islam never teaches a hedonistic lifestyle as it can be detrimental to individuals and society. Such a life pattern can lead to extravagance, whereas Islam advocates living according to one's needs (maslahah). A hedonistic lifestyle can be detrimental to the younger generation, especially students.